The Architectonics of Information: Ancient Topical Thought and Postmodern Information - Catherine L. Hobbs (Journal of the Assembly for Expanded Perspectives on Learning, 1999)
This paper examines the usefulness of thought patterns from ancient rhetoric as they have been appropriated historically and as potentially applicable concepts for the present and future in today's interlinked electronic environment. An earlier version of this paper, first delivered as part of a panel at the Rhetoric Society of America meeting at Tucson in May 1 996, was delivered and published as "The Architectonics of Information: Ancient Topical Thought and Postmodern Cognition" in Proceedings of the Mid-America Symposium on E merging Computer Technologies, October 1 996. (The published papers are available in "Information Problems" at http://www.ou.edu/cas/english/agora/). I would like to thank Jana Moring and Dianne Juby for their collaboration on the panel.